TEACHER CORRECTIVE FEEDBACK IN TEACHING SPEAKING AT SMAN 1 BATUKLIANG - Agus Jayadi; Muhamad Suhaili; I Made Permadi Utama (Sinar Lima, 2025)
English speaking play a vital role in global education and communication. In today’s globalized world, English speaking proficiency is not just an additional skill, but a fundamental requirement that supports various aspects of life, including education, business, and international relations. However, teaching speaking skills presents a number of challenges, including students’ lack of confidence, grammatical errors, mispronunciation, and limited vocabulary. This study aims to identify the types and frequency of feedback used by teachers in teaching speaking at SMAN 1 Batukliang. This study used a qualitative method with observation and interview instruments. The results showed that oral feedback was more dominant than written feedback. The types of oral feedback used included explicit correction, repetition, positive feedback, and metalinguistics. Meanwhile, written feedback applied was only positive feedback. In terms of frequency, oral feedback was given six times, while written feedback was only given once, with feedback most often occurring in the main activity and pre-activity stages. Teachers at SMAN 1 Batukliang used more oral feedback to correct mistakes and motivate students. Although written feedback was limited, this approach succeeded in creating a supportive learning environment.